Pelatihan Public Speaking Bagi Kader PKK Kelurahan Bendungan Hilir Jakarta Sebagai Tenaga Penyuluhan Penanganan Stunting - Sungkono, Nono; Pasaribu, Mukka; Santoso, Prasetya Yoga; Dewi, Yuni Retna; Ridwan, Widyarini; Hamsinah, Hamsinah (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Community service activities have the aim of empowering the community through public speaking training for PKK cadres in the Bendungan Hilir subdistrict of Jakarta. Providing information to the public: how big is the role of public speaking in outreach to the community This training activity was carried out at RPTRA Taman Guntur Jl. Danau Bratan No. 3, RT.10/RW 3, Bendungan Hilir, Tanah Abang sub-district, Central Jakarta City, a special area of the capital city of Jakarta. The residents who attended were mostly active PKK cadres. The method used in this activity is in the form of lectures and public speaking training for outreach to the community. Residents are also taught how to be ethical and prepare for public speaking. Public speaking training for PKK cadres at Bendungan Hilir Jakarta City can be an effective tool in dealing with stunting. Public speaking skills can be used to increase public awareness, disseminate accurate information, and encourage behavioral changes related to diet and child nutrition. With careful preparation, a clear structure, effective use of language, and frequent practice, PKK cadres can improve their public speaking skills and become more reliable speakers in their efforts to deal with stunting.